METHODS FOR CONTROLLING THE INTERFACE STRUCTURE BETWEEN MATRIX AND REINFORCEMENT IN COMPOSITE MATERIALS (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes the interface and interphase structure between matrix and reinforcing fibers in fiber-reinforced polymer (FRP) composites, their influence on mechanical properties and load transfer mechanisms. Interface degradation, microcrack formation, and environmental effects are discussed. Theoretical models and experimental methods are also reviewed.